Tax Revenue of Nepal: Assessing the Impact on GDP - Kharel, Khom Raj (Interdisciplinary Journal of Management and Social Sciences, 2021)
This study examines the economic impact of tax revenue and economic growth of Nepal, from 2000 to 2018. In order to attain the objectives, relevant time-series secondary data were collected from the Economic Survey published by Ministry of Finance, Quarterly Economic Bulletin published by Nepal Rastra Bank, Revenue  Department and previous works done by scholars. The collected data has been analyzed by using linear regression model. The results display that tax revenue and total revenue has a positive significant effect on GDP. The trends of tax revenue has signified the positive trends but not sufficient to meet the government expenditure of Nepal.